Increasing Research Capacity in a Safety Net Setting Through an Academic Clinical Partnership. (June 2017) - Brooks Carthon, J. Margo; Holland, Sara; Gamble, Kerry; Rothwell, Helyn; Pancir, Darcy; Ballinghoff, Jim; Aiken, Linda
Abstract : Safety net settings care for a disproportionate share of low-resource patients often have fewer resources to invest in nursing research. To address this dilemma, an academic-clinical partnership was formed in an effort to increase nursing research capacity at a safety net setting. Penn Presbyterian Medical Center and the Center for Health Outcomes and Policy Research located at the University of Pennsylvania partnered researchers and baccalaureate-prepared nurses in an 18-month research skill development program. This article describes the programmatic design, conceptual framework, resource requirements, and effect on the institutional partners and participants.